(untitled) (Journal of English Language Teaching and Education (JELTE), 2022)
This research is the result of research on students’ anxiety in learning English by students of SMPN 03 Mempawah Hilir, West Kalimantan. Anxiety in learning English is often reported to negatively affect English learning. This research aims to determine the level of anxiety and the factors that dominate the anxiety of students at SMPN 03 in Mempawah Hilir, West Kalimantan in learning English, which will then be carried out further research to respond to the findings in this research. The method used in this research is descriptive approach, where the findings are presented in the form of a description of the calculations from the data obtained from questionnaires and interviews. This research took junior high school students in one class as respondents. They are class VII A students in 2021/2022. Questionnaires and interviews were distributed to collect data on students’ anxiety in learning English. The questions in the questionnaire were made to determine the level of students’ anxiety in learning English but interviews were conducted to determine the factors that dominate students’ anxiety in learning English. The data obtained from the questionnaire will be calculated the average and percentage. Then the value obtained will be categorized such as mild anxiety, moderate anxiety, severe anxiety, and panic. From the results of interviews with students, conclusions will be drawn to see the similarities experienced by students. It was found that level of students’ anxiety in this school is severe anxiety. In mild anxiety, the average result is (59%) with enough criteria. On moderate anxiety, the average result is (57%) with enough criteria, (67%) of severe anxiety belongs to the strong criteria. There is a (47%) average score on panic anxiety that belongs to the enough criteria. Based on the results of these percentages, students are in the Severe Anxiety. From the results of the interview, it was found that the factor that dominates students’ anxiety in learning English is test anxiety. All respondent are 24 students of class VII A in 2021/2022.